The Paris notebook [large type] - Harris, Tessa (Thorndike Press, a part Gale, a Cengage Company, 2024)
"January 1939: When Katja Heinz secures a job as a typist at Doctor Viktor's clinic, she doesn't expect to be copying top secret medical records from a notebook. At the end of the first world war, Doctor Viktor treated soldiers for psychological disorders. One of the patients was none other than Adolf Hitler. . . The notes in his possession declare Hitler unfit for office - a secret that could destroy the Führer's reputation, and change the course of the war if exposed. . . With the notebook hidden in her hat box, Katja and Doctor Viktor travel to Paris. Seeking refuge in the Shakespeare and Company bookshop, they hope to find a publisher brave enough to print the controversial script. But Katja is being watched. Nazi spies in Paris have discovered her plan. They will stop at nothing to destroy the notebook and silence those who know of the secret hidden inside. . ."--Publisher.